Понедельник начинается в субботу: [фантастический роман] / Аркадий и Борис Стругацкие - Стругацкий Аркадий Натанович (АСТ, 2015)
Экземпляры: АБ (20201028) / Инвентарный номер: 54814z1 / Цена: / Авт.знак: С 87 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6